Anthelmintic resistance in commercial sheep farms in Costa Rica - Castro Arnáez, Isabel Cristina (2021)
Forty-eight commercial sheep farms were sampled between the years 2017 and 2019 to evaluate the percentage of reduction of the three families of broad-spectrum anthelmintic drugs available in Costa Rica - benzimidazoles (albendazole), macrocyclic lactones (ivermectin) and imidazothiazoles (levamisole) - in grazing animals by using the fecal egg count reduction test. Animals were selected based on their egg per gram counts after their fecal samples were processed by a modified McMaster technique. The remaining fecal samples were taken to the laboratory for fecal culture and larval identification. The prevalence of farms with albendazole resistance was 100%, ivermectin 96% and levamisole 17%. Seven (n = 47) farms resulted with triple resistance, 39 with double and 1 farm was resistant to 1 AH tested. Haemonchus spp. was the most commonly isolated parasite in pre- and post-treatment larval culture. This is the first report of Oesophagostomum spp. and Teladorsagia sp. resistant to albendazole, Oesophagostomum spp., Teladorsagia sp., Chabertia sp. and Cooperia sp. resistant to ivermectin, and the presence of strains of Haemonchus spp. and Trichostrongylus sp. resistant to the 3 anthelmintics tested. The results of this study demonstrate that anthelmintic resistance is widespread, particularly in Haemonchus spp., and that the major drugs available in the country have lost much of their effectiveness against sheep nematodes.